Implementasi Reward Asyik dalam Meningkatkan Rasa Percaya Diri Anak Kelompok B TKIT Almarjan Bekasi - Alis Hamidah; Anis Diah Utami; Iting Sugiarti; Ummul Faizah Rohmatin; Rofiati Rofiati; Sri Watini (Jurnal Syntax Admiration, 2024)
Early Childhood Education is an effort to provide stimulus for children from birth to six years of age. Education during the golden age is carried out to help children's growth and development, both physically and spiritually, so that children are ready to enter further education. One aspect of development is social emotional development, including self-confidence. This research aims to increase the self-confidence of children aged 5-6 years through "Reward ASYIK" at TKIT Almarjan Bekasi. This research uses qualitative descriptive with observation, interviews and documentation of children's self-confidence. This research was conducted from 10 October to 28 November. The results of the research show that there is a significant increase in children's self-confidence by giving fun rewards, namely by shouting "I can, I'm great, I'm successful, yes!!!" spoken well by all children with a total of 17 children, 3 children had high self-confidence. 11 are as expected, 2 children are starting to develop and 1 child is not yet developing. This research concludes that "Reward ASYIK" is effective in increasing the self-confidence of group B children at TKIT AlMarjan Bekasi.